2014
DOI: 10.1111/rda.12270
|View full text |Cite
|
Sign up to set email alerts
|

Concentration, Activity and Biochemical Characterization of Myeloperoxidase in Fresh and Post‐Thaw Equine Semen and their Implication on Freezability

Abstract: Myeloperoxidase (MPO) is a pro-oxidant enzyme associated with decreased motility in thawed equine semen. This study aimed to describe MPO concentration, activity and subunits in raw and thawed semen and to correlate these data with motilities in raw and thawed semen. Semen samples from five stallions were collected four times. Motilities were assessed in raw and thawed semen. MPO assays were performed in raw seminal plasma, raw sperm-rich pellet and thawed semen. Total and active MPO concentrations were, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In addition, some molecules seem to be able to inhibit plasma MPO by different mechanisms and at different degrees [74][75][76][77] but, to our knowledge, they have not been studied in uterine fluid yet. Furthermore, in equine sperm supernatant, where high concentrations of total MPO are also observed, Ponthier et al [20] showed an important presence of MPO precursor. Unlike in the human [2], the enzyme precursor is inactive in the equine [38] and is then cleaved into the active subunit of the enzyme.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, some molecules seem to be able to inhibit plasma MPO by different mechanisms and at different degrees [74][75][76][77] but, to our knowledge, they have not been studied in uterine fluid yet. Furthermore, in equine sperm supernatant, where high concentrations of total MPO are also observed, Ponthier et al [20] showed an important presence of MPO precursor. Unlike in the human [2], the enzyme precursor is inactive in the equine [38] and is then cleaved into the active subunit of the enzyme.…”
Section: Discussionmentioning
confidence: 97%
“…In horses, MPO has been identified, both under active and inactive form, in various fluids and tissues [18][19][20][21] and has been shown to be involved in numerous inflammatory processes [18,19,[22][23][24]. Some studies have focused on MPO and its implications in pathological conditions of the endometrium, such as endometritis and endometrosis [24][25][26][27], which are a major cause of infertility in the mare that adversely impact the horse breeding industry.…”
Section: Introductionmentioning
confidence: 99%
“…As these lightweight MPO bands were previously detected by Ponthier et al (2014) in horse semen, we decided to determine whether MPO was also present in the epididymal and ejaculated ram spermatozoa. IFI analyses revealed that MPO is located in the postacrosomal region of all spermatozoa, with some of them showing a bright band in the equatorial region.…”
Section: Discussionmentioning
confidence: 99%
“…The approval of artificial insemination usage in horse breeding programs by most breed associations intensified research on this biotechnology, particularly due to its potential for semen storage from valuable stallions for unlimited periods of time. However, fertility rates using horse frozen-thawed semen is consistently lower than in other species [4,30], thus suggesting that horse semen is particularly sensitive to cryoinjury [19,33].…”
Section: Introductionmentioning
confidence: 99%
“…Semen cryotolerance in horses depends upon genetic factors and cryopreservation protocol [2,38], such as diluent and cryoprotectant choice [2,28]. For these reasons, the effect of individual stallions has been extensively investigated throughout the years, aiming to identify factors associated to semen cryotolerance in horses, especially for stallions classified as holding low semen freezability potential [12,15,18,32,33,39].…”
Section: Introductionmentioning
confidence: 99%